2011
DOI: 10.1186/1477-9560-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Sequential thrombosis and bleeding in a woman with a prolonged activated partial thromboplastin time

Abstract: Simultaneous or sequential haemorrhage and thrombosis in the presence of a prolonged activated partial thromboplastin time (aPTT) is a rare occurrence: we describe the case a 37 year old lady who developed post-delivery deep vein thrombosis treated with low molecular heparin and warfarin followed a week later by extensive bruising over legs and forearms, a significant drop in haemoglobin and a very prolonged aPTT. Further tests revealed an acquired factor VIII inhibitor at 35 Bethesda Units. We discuss the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The mode of presentation remains similar even with the variation in the days of occurrence. Our patient reported the occurrence of a massive hemorrhagic disease on the very first day post-LSCS, while Spencer et al [ 9 ] have reported the occurrence of massive hematomas in a primigravida five weeks post-LSCS. In another study, Lee et al [ 8 ] have reported a vaginal bleed five days after the LSCS, and the development of large hematomas 65 days after the LSCS.…”
Section: Discussionmentioning
confidence: 53%
“…The mode of presentation remains similar even with the variation in the days of occurrence. Our patient reported the occurrence of a massive hemorrhagic disease on the very first day post-LSCS, while Spencer et al [ 9 ] have reported the occurrence of massive hematomas in a primigravida five weeks post-LSCS. In another study, Lee et al [ 8 ] have reported a vaginal bleed five days after the LSCS, and the development of large hematomas 65 days after the LSCS.…”
Section: Discussionmentioning
confidence: 53%
“…We identified 15 cases of an LA coexisting with AHA (n ¼ 14) and AHB (n ¼ 1) where the laboratory presentation was a prolonged aPTT: the initial clinical presentation was vascular occlusion in 6 cases [6][7][8][9][10][11] and bleeding in 9 cases. 9,[12][13][14][15][16][17][18] The different tests to diagnose LA, FVIII levels, and its inhibitors are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Vessel occlusion was the clinical presentation in 6 of the 15 cases of which 5 were deep vein thrombosis (DVT) 6-10 and 1 was ischemic stroke. 11 Of the 5 DVT cases, 2 developed postpartum, 6,9 1 in the absence of an underlying disorder, 7 1 during the course of non-Hodgkin lymphoma, 8 and 1 during treatment for chronic lymphoid leukemia. 10 Ischemic stroke developed in 1 patient with AHB having underlying insulin-dependent diabetes mellitus.…”
Section: Coexistent La and Ah Presenting As Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a literature review and identified nine cases of patients with acquired hemophilia A and concurrent thrombosis ( Table 1 ). 13 15 16 17 18 19 20 Most cases described the development of bleeding on the background of ongoing treatment for venous thrombosis. Several cases in the literature also discuss the difficulty of discriminating a DVT from an intramuscular hematoma or bleeding, with superimposed bruising and secondary extrinsic venous outflow obstruction.…”
Section: Discussionmentioning
confidence: 99%